(untitled) (Journal of Hama University, 2024)
The research was carried out at Alsanobar Research Station – Lattakia – General Commission for Scientific Agricultural Research. During the two seasons 2020–2021 to determine the effect of two irrigation methods on two different fertilizers recommendations of the tomato crop (Lycopersicom esculentum) on some of the studied indicators under protected agriculture conditions. Two main treatments for irrigation methods (drip irrigation R1, surface irrigation R2), and within each irrigation treatment there were Two secondary fertilizer treatments (T1 treatment according to a productivity of 6 tons, T2 Ministry’s treatment) in Three replications by using split plots. The R1 irrigation method recorded the highest efficiency of fertilizer use through its superiority in the studied indicators. The results also showed the efficiency of the fertilizer equation used to estimate the amount of fertilizer to be added, as the T1 treatment recorded the highest values for the studied indicators in terms of plant height, productivity, weight of 10 Fruits, and the wet weight of the plant, with significant differences compared to the T2 fertilization treatment recommended by the Ministry. Through the interaction between the two factors, the best values were for treatment R1T1 and the lowest values were for treatment R2T2.